2010
DOI: 10.5539/ass.v6n7p91
|View full text |Cite
|
Sign up to set email alerts
|

Sufficiency Community Economic Development System: A Pathway to Sustainable Community Development in Thailand

Abstract: This study addressed an alternative approach, sufficiency economy approach, to be applied in community economic development which can be referred as "sufficiency community economic development -SCED". SCED concerns on a holistic approach of CED activities through community participation that focuses on the capacities and livelihoods of community in order to enhance the community strengths and members' livelihoods. SCED requires that activities are developed based on community-demand with a firm foundation of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…Therefore, the impact is broader and similar to Suwankitti and Pongquan (2010) findings regarding SEA impacts. Nevertheless, there is no absolute assurance that the community economy project will success and beneficial in all contexts (Crawford et www.ccsenet.org/ass Asian Social Science Vol.…”
Section: Sufficient and Sustainable Livelihoodsupporting
confidence: 57%
See 3 more Smart Citations
“…Therefore, the impact is broader and similar to Suwankitti and Pongquan (2010) findings regarding SEA impacts. Nevertheless, there is no absolute assurance that the community economy project will success and beneficial in all contexts (Crawford et www.ccsenet.org/ass Asian Social Science Vol.…”
Section: Sufficient and Sustainable Livelihoodsupporting
confidence: 57%
“…For example, Hart (2011) implicitly showed that the agricultural based project has provided livelihood for poor farmers in the rural village of South Africa. Besides, a study by Suwankitti and Pongquan (2010) also found that the operation of an agro-based community economy development activity in Bhuttavimut supported the adoption of sufficient livelihood approach for local people. Therefore, agricultural activity is a suitable platform to operate the community economy among rural villagers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It focuses on moderation, reasonableness, self-immunity, based on knowledge and moral conditions, for balanced and sustainable economic development. Studies have applied this concept to develop community enterprises and strengthen communities (Singhamat, 2017;Sarapirom & Sarkar, 2018). d) To efficiently drive the economy, knowledge-based economies emphasize the development of labor skills, information technology, and an appropriate business environment.…”
Section: Small and Micro Community Enterprise Policymentioning
confidence: 99%